Intergenerational transfer of health inequalities: exploration of mechanisms in the Birth to Twenty cohort in South Africa - Linda Richter; Dieter von Fintel (BMJ Global Health)
South Africa’s history of colonialism and Apartheid contributed to its extreme levels of inequality. Twenty-five years after the transition to democracy, socio-economic and health inequalities continue to rank among the highest in the world. The Birth to Twenty+ study follows a cohort born in urban Johannesburg in 1990 through their early lives and into young adulthood. Also known as ‘Mandela’s Children’, these ‘children of the ‘90s’ were the first generation to be raised in a democratic society, whose elected government implemented policies to achieve greater socio-economic and health equality. Correlating early life outcomes to those of their parents provides a baseline estimate of intergenerational transmission of historical inequality. Analyses of their early life course indicates the potential breakdown in inequality in the first generation. This paper provides an overview of empirical results on intergenerational change in socio-economic status and health during South Africa’s political transition. Access to infrastructural services improved, and poverty reduced following the rapid expansion of unconditional cash transfers mainly to children and pensioners. However, unemployment remained high and job discrimination continued. Inequalities in health follow similar patterns, and progress did not equate to convergence. Some catch-up physical growth occurred—both across groups and over time—but not sufficient to bridge cognitive inequalities. Socio-economic and health inequalities continued as the children of the ‘90s reached young adulthood. Based on knowledge of other transitions, it is likely that these inequalities will only start to break down in later generations, provided social and economic progress holds steady.